ANALISA PEMELIHARAAN ALAT ELECTROLYTE ANALYZER MERK SPOTCHEM EL SE-1520 - Nagata, Geosandy; Priyulida, Fitria (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2022)
Health equipment is one of the factors that holds important equipment in providing health services to the community so that maintenance activities are needed for the sake of survival and the quality of the results of the tool, one of which is an electrolyte analyzer.Electrolyte analyzer is a laboratory equipment needed to determine electrolyte levels in the human body